INTERPERSONAL COMMUNICATION OF THE MANDAILING ETHNIC GROUP IN PRESERVING THE MANGAMBAT BORU TRADITION IN SIBORANGAN LABUHANBATU - Puspita Simbolon; Suheri Harahap (Program Pascasarjana UIN Sumatera Utara, 2026)
This study examines how interpersonal communication sustains the Mangambat Boru tradition among the Mandailing ethnic community in Siborangan, Labuhanbatu, amid intergenerational and socio-cultural change. The study is novel in positioning interpersonal communication not merely as a medium of cultural transmission, but as a social mechanism through which kinship values, symbolic meaning, and customary legitimacy are continuously negotiated across generations. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation involving traditional leaders, parents, and young people. The findings show that the preservation of Mangambat Boru relies on three interconnected communication forms: verbal communication through advice and dialogue, nonverbal communication through symbolic gestures and customary etiquette, and participatory communication in family and customary forums. However, this process is constrained by generational differences, limited comprehension of traditional language, and the declining intensity of face-to-face interaction in the digital era. The study contributes theoretically by reinforcing the view that interpersonal communication in cultural contexts functions not only to convey messages, but also to mediate meaning, authority, and adaptation within living traditions. Practically, the findings suggest that the preservation of local tradition requires adaptive communication strategies that are dialogical, culturally grounded, and responsive to the communicative preferences of younger generations.